The clinical use of epigenetics in psychiatry: a narrative review of epigenetic mechanisms, key candidate genes, and precision psychiatry - Montel Hayes, Rachel; Mason, Christopher E.; Miller, John J. (Frontiers in Psychiatry, 2025)
The etiology of psychiatric disorders is complex, involving both genetic and environmental factors with emerging evidence suggesting that epigenetic modifications, including DNA methylation, histone modifications, and non-coding RNA regulation, significantly contribute to mental health. The epigenome influences the development of psychiatric disorders and human behavior and may be considered in clinical observations. Epigenetic changes have been well-established in BDNF, COMT, FKBP5, NR3C1, SLC6A4, and DRD2, genes associated with psychiatric disorders, including schizophrenia, major depressive disorder (MDD), bipolar disorder (BP), post-traumatic stress disorder (PTSD), and autism spectrum disorder (ASD). Therefore, these epigenetic marks have the potential to be suitable biomarkers for diagnostics, as predictors of prognosis, and for the development of personalized treatments. By exploring the role of clinically relevant epigenetic genes, we review the role of the epigenome in the context of psychiatric disorders and human behavior; and we consider that these changes may be observed in the context of precision psychiatry. This review synthesizes findings from over 100 original research articles and reviews spanning a range of clinical studies. Despite promising associations, challenges in the onset of precision psychiatry, such as tissue heterogeneity, small sample sizes, and lack of replication, are likely to limit translation into clinical practice. Future research in precision psychiatry will help identify clinically actionable epigenetic biomarkers, ushering in an era of genomic medicine in psychiatry.